Kesejahteraan Psikologis Pada Narapidana di Lembaga Pemasyarakatan Kelas II A Sragen - PRATAMA, Farkhan Ari (2016)
The lives of prisioner at the Correctional Institution is a form of punishment for the consequences of unlawful behavior ever conducted. The problems experienced by prisioner to live a life in Prison, including a change of life, loss of freedom and rights are more limited, until the acquisition of villain label inherent and lives in Penitentiary making them must be separated from their families and live with other prisioner. Title as an inmate is not something that can easily be accepted by someone, but indirectly prisioner are required to account for criminal acts that he did, and then were able to have self-acceptance, have positive relationships with others, have a way in the mastery of the environment, and has a purpose life. The aim of this study was to describe the dynamics of Psychological Well-Being of Prisoners in Penitentiary In Class IIA Sragen. The informants as many as four people were selected by purposive sampling characteristics, among others: a) prisioner aged 21 to 50 years, b) the prisioner is serving a sentence and a half or more, and c) the prisioner were first inhabited the prison, not convicts. This study using interviews and observation. The results of this study are prisoners who have psychological well-being is that they are able to adapt to the environment, having good social relationships, able to relieve stress, so as to create a state according to the condition of his soul, and has a life expectancy for the better and not to repeat the act again , While prisioner who do not have the psychological well-being, those who do not have good social relationships and have no way to cope with stress.